To determine the zeros of the quadratic function \(y = 2x^2 + 9x + 4\), we need to solve the equation \(2x^2 + 9x + 4 = 0\).
We can use the quadratic formula:
\[ x = \frac{{-b \pm \sqrt{{b^2 - 4ac}}}}{{2a}} \]
where \(a = 2\), \(b = 9\), and \(c = 4\).
First, we calculate the discriminant (\(D\)):
\[ D = b^2 - 4ac = 9^2 - 4(2)(4) = 81 - 32 = 49 \]
Since the discriminant is positive, there are two real and distinct solutions.
Now we substitute the values into the quadratic formula:
\[ x = \frac{{-9 \pm \sqrt{49}}}{{2 \cdot 2}} = \frac{{-9 \pm 7}}{4} \]
Now we have two solutions to compute:
- \(x = \frac{{-9 + 7}}{4} = \frac{{-2}}{4} = -0.5\)
- \(x = \frac{{-9 - 7}}{4} = \frac{{-16}}{4} = -4\)
Thus the zeros of the quadratic function are:
\[ (-4, 0) \quad \text{and} \quad (-0.5, 0) \]
So the correct response is:
(−4,0)(−0.5,0)